A Phenomenological Study On How Student Experience And Perception "The Internship Program" At Universitas Muhammadiyah Surakarta - SINTA ARDANARI, MARIA; , Fitri Kurniawan, M. Res, Ed (2017)
This research discuss the students experience and understand the internship program at Universitas Muhammadiyah Surakarta. The purpose of the research to examine the experience and understanding of students about internship program. Types of this research is phenomenological hermeneutic. The research subjects is student of the seventh semester. Collecting data in this research using semi structure interview (in depth). Data validity is member checking. The results of this research demonstrate their experience and understanding of students about internship programs; (1) Internship programs as job training and practice professionalism, (2) Activity of internship 1 is observation about the school environment, (3) The implementation a internship programme classified into three times and internship 1 for two weeks.